Synergistic effects of Pandanus fascicularis extracts and azithromycin: in vitro and in silico antimicrobial investigation against MDR clinical strains - Khatun, Mst. Hajera; Islam, Md Rashedul; Khatun, Shikha; Zalah, Amro Ahmed; Rony, Md. Hadisur Rahman; Khatun, Mst. Munira; Wasili, Emad Essa A.; Barmon, Jaytirmoy; Sami, Saad Ahmed; Masmali, Abdulrahman Hadi; Qadri, Ishtiaq (Frontiers in Antibiotics, 2025)
BackgroundAntibiotic-resistant bacteria are becoming a significant global concern. To combat the spread of resistance or reverse multidrug resistance, developing novel antimicrobials and/or resistance modulators is essential. This study aimed to evaluate the synergistic effects of the methanolic extract of Pandanus fascicularis fruits (MEPFF) in combination with azithromycin against multidrug-resistant bacteria.MethodsPhytochemical analysis along with the determination of total phenolic content (TPC), total flavonoid content (TFC), and total antioxidant capacity (TAC) of MEPFF, was performed using standard procedure. The extract's DPPH free radical scavenging activity was assessed to evaluate its potential antioxidant activity. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of MEPFF against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa were determined, followed by an analysis of the synergistic effect with azithromycin, as well as the activity of azithromycin alone. Subsequently, the drug-likeness, antibacterial activity, and toxicological properties were analyzed using in silico tools.ResultsThe quantitative investigation found terpenoids, flavonoids, tannins, phenolics, saponins, cardiac glycosides, and alkaloids in MEPFF. The TFC, TPC, and TAC of MEPFF were found at 183 ± 9.54 mg QE, 248.33 ± 11.06 mg GAE, and 95.33 ± 8.33 mg AAE/gm extract. The extract showed significant antioxidant activity in the DPPH experiment, with an IC50 value of 12.13±0.53 µg/ml. Azithromycin and the extract together have far greater antibacterial action against all four bacterial strains. The minimal inhibitory concentration (MIC) is 3.67 ± 1.15 to 5.83 ± 0.76 mg/mL, while the minimum bactericidal concentration (MBC) is 4.33 ± 1.26 to 7.33 ± 1.04 mg/mL. In silico studies revealed that pandamarilactone-1, nonpandamarilactone-B, and thiamine had the best docking energy (−9.9, −8.9, and −8.5 kcal/mol), suggesting most active compounds against MPh-II protein.ConclusionThe extract enhances antibiotic therapy and suggests that the aforesaid synergistic drug-herb combinations may treat MDR bacterial infections.